The role of mental illness in women’s pathways to crime living in a U.S.-México border region - Adair, Rebekah (Psychology, crime & law, 2026)
Feminist criminological theories emphasize trauma and victimization as pathways to criminal behavior among women while gender-neutral theories suggest that mental illness has a weak relationship to criminal behavior. Unfortunately, research on pathways to criminal behavior for women from different ethnic and cultural backgrounds is scant. The present study used semi-structured interviews to qualitatively examine factors that paved the pathway to criminal behavior for 72 women living in the U.S.-México border region. Four undergraduate research assistants coded the interviews and demonstrated acceptable reliability (Kappa = 0.72). Women frequently reported that financial issues, substance use, and family problems were direct causes of their criminal behavior. Moreover, even though a Structured Clinical Interview (SCID-IV) revealed many women met criteria for a diagnosable mental disorder and/or had experienced trauma, mental illness and trauma were rarely reported as direct causal factors of criminal behavior. Findings suggest agencies may be more successful at reducing recidivism if they allocate resources to assist women residing in border regions with: (1) accessibility to substance abuse interventions, (2) developing skills to resolve familial conflict, and (3) having ample opportunities to become gainfully employed.